Value of the financial analysis for successful development of the enterprise (Journal of Economic Research & Business Administration, 2016)
subject of attention of an extensive circle of participants of the market relationsinterested in results of its functioning. Practically all users of financialstatements use methods of the financial analysis for decision-making onoptimization of the interests. Heads and the relevant services, and alsofounders for the purpose of studying of effective use of resources, increaseof profitability of the capital, ensuring stability of position of the enterpriseare engaged in the analysis of a financial condition of the enterprise, organization.Owners analyze the reporting for increase of profitability of thecapital, ensuring stability of position of the enterprise. Creditors and investorsanalyze financial reports to minimize the risks on loans and deposits,suppliers - for timely receiving payments, the tax inspections - for implementationof the plan of receipt of funds in the budget etc. It is possible tosay firmly that quality of the made decisions entirely depends on quality oftheir analytical validity.
Keywords: financial analysis; financial statements; creditors.